(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study aimed to know the impact of the capital structure measured by the ratio of financing to short-term capital and the ratio of financing to long-term capital on the profitability of companies, as measured by the rate of return on assets and the rate of return on equity. The study was applied to industrial sector companies listed in the Iraq Stock Exchange. The financial number of (14) companies, and (4) companies were selected that met the conditions for selecting the study sample. The study methodology relies on the analytical method as it is more appropriate to the nature, scope and objectives of the study, and the ready-made statistical program "SPSS" will be used to analyze the relationships and influence between the study variables and test the hypotheses.